Historical and geopolitical analysis of Nūr Al-Dīn Mahmūd Zankī’s Plan for liberating Bayt Al-Maqdis - Burhan Che Daud; Abd al-Fattah El-Awaisi; Mohd Roslan Mohd Nor (Beytülmakdis Çalışmaları Vakfı, 2018)
Nūr al-Dīn Mahmūd Zankī was one of the 6th century AH Muslims leaders who particularly had thought very carefully of how to liberate Bayt al-Maqdis. The main objective of this article is namely to examine Nūr al-Dīn’s preparation plan to liberate Bayt al-Maqdis, in particular if he had prepared the ground to achieve such a goal which was successfully accomplished during the time of his successor, Salāh al-Dīn al-Ayyūbī. In addition to the religious impact, this article examines the remaining material evidence and the practical steps that had been taken by Nūr al-Dīn throughout twenty-eight years of his career to construct a strong and a solid argument concerning his clear and distinctive plan towards liberating Bayt al-Maqdis. The main focus is on examining his preparation steps towards the unification of Syria and afterwards the unification of Syria with Egypt.